Business Cooperation between China and Slovenia: The Importance of Intercultural Understanding for the Success of Economic Relations - Lazič, Anastazija; Vukovič, Goran (Prometna varnost v lokalnem okolju: problemsko-učno sodelovanje z Intermatic d.o.o., 2026)
We discuss business cooperation between China and Slovenia and the importance of intercultural understanding for the success of economic relations. In recent decades, China has become one of the world's leading economic powers, which was also reflected in the increased presence of Chinese investments in Europe and Slovenia. Due to differences in business culture, communication styles and organizational practices, intercultural understanding has been an important factor in successful cooperation in international companies. The purpose of the research was to determine how employees experience intercultural cooperation and how communication, empathy and adaptability affect teamwork, conflicts and employee satisfaction. The results of the research showed that employees mostly evaluate intercultural cooperation positively. Employee satisfaction was rated the highest, while empathy and adaptability of employees and management also played an important role. Intercultural communication was rated slightly lower, indicating the presence of certain communication challenges between Slovenian and Chinese colleagues. We found that better communication contributes to more effective teamwork, a higher level of empathy reduces the occurrence of conflicts, and adaptability has a positive impact on employee satisfaction. The research thus contributed to a better understanding of the factors that influence the success of business cooperation between Slovenian and Chinese companies.